Dynamic Multiplex Tissue Imaging in Inflammation Research - Uderhardt, Stefan; Neag, Georgiana; Germain, Ronald N. (Annual Reviews Inc., 2024)
Inflammation is a highly dynamic process with immune cells that continuously interact with each other and parenchymal components as they migrate through tissue. The dynamic cellular responses and interaction patterns are a function of the complex tissue environment that cannot be fully reconstructed ex vivo, making it necessary to assess cell dynamics and changing spatial patterning in vivo. These dynamics often play out deep within tissues, requiring the optical focus to be placed far below the surface of an opaque organ. With the emergence of commercially available two-photon excitation lasers that can be combined with existing imaging systems, new avenues for imaging deep tissues over long periods of time have become available. We discuss a selected subset of studies illustrating how two-photon microscopy (2PM) has helped to relate the dynamics of immune cells to their in situ function and to understand the molecular patterns that govern their behavior in vivo. We also review some key practical aspects of 2PM methods and point out issues that can confound the results, so that readers can better evaluate the reliability of conclusions drawn using this technology.
CRIS-Team Scopus Importer:2024-02-16
Keywords: dynamic imaging; intravital imaging; multiplex imaging; tissue imaging; two-photon microscopy